CODED VS UNCODED CORRECTIVE FEEDBACK IN TEACHING WRITING DESCRIPTIVE TEXT - Siska Rizkiani; Gartika Pandu Bhuana; Rissa San Rizqiya (STKIP Siliwangi, 2020)
Written Corrective Feedback (WFC) has been in dispute for several decades whether it is effective or ineffective. This study aims at finding out whether there is difference between students who are taught by giving indirect coded feedback and those who are given indirect uncoded feedback. Quasi experimental applied in conducting this research. 35 students in control group were given uncoded feedback, and 35 students in experimental were given coded feedback. The result of descriptive statistic revealed that indirect writing corrective feedback statistically improved the students’ writing score. Furthermore, there was a significant mean difference in students’ score between the students who were given coded and those who received uncoded writing corrective feedback.